2019
DOI: 10.1155/2019/3893049
|View full text |Cite
|
Sign up to set email alerts
|

Patient’s Preference on Neurosurgeon’s Attire and Appearance: A Single Center Study in Korea Cross-Sectional Study

Abstract: Objective. This study was performed to assess neurosurgery patients’ preference for surgeon’s attire and appearance in the hospital. Methods. A total of 100 patients were investigated using a questionnaire comprising 13 questions. We first asked patients about neurosurgeon’s appearance including accessories, hair color, mustache, and beard. Then, based on their preferences, they were asked to rank a series of photographs which illustrated a variety of neurosurgeon attires worn by a doctor. Results. Professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Other studies exploring patient perceptions for physician attire have yielded a diverse and often conflicting array of findings, most of which are complicated by different measurement tools and outcomes. Consistent with our results, numerous studies across continents have identified a clear patient preference for white coats 6 7 10 12 14 23 25–41. However, some studies reveal no significant preferences,42–45 and others indicate that the white coat may even cause higher levels of tension in patients 44.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Other studies exploring patient perceptions for physician attire have yielded a diverse and often conflicting array of findings, most of which are complicated by different measurement tools and outcomes. Consistent with our results, numerous studies across continents have identified a clear patient preference for white coats 6 7 10 12 14 23 25–41. However, some studies reveal no significant preferences,42–45 and others indicate that the white coat may even cause higher levels of tension in patients 44.…”
Section: Discussionsupporting
confidence: 90%
“…Physician attire is an important element in establishing patient confidence and trust, 6 enhancing patient comfort when discussing personal problems [7][8][9] and shaping patient perceptions of physician professionalism, 6 intelligence 10 and empathy. 11 Most prior scholarship has focused on a single geographic region, country or clinical context (eg, primary care clinic, hospital setting) [12][13][14][15] and has not considered the relative impacts of different physician specialties, contexts of care, geography and patient factors such as age, education and gender. In addition, heterogeneity among prior studies, such as different sampling methodology and survey instruments, has made comparisons across different studies challenging.…”
Section: Open Accessmentioning
confidence: 99%
“…Publications that addressed professional identity were sometimes philosophical and sometimes practical. 10,15-65 Several articles addressed the concept of excellence in neurosurgery, 31-33,35,36 while others addressed the personality of a neurosurgeon. 20,61,62 Twelve of the indexed publications were presidential speeches from past presidents of the Congress of Neurological Surgeons (CNS), American Association of Neurological Surgeons (AANS), and several international neurosurgery societies.…”
Section: Resultsmentioning
confidence: 99%
“…16,17,20,26,28,30,39,43,[45][46][47]66 One article explored the patient perception of neurosurgeons' appearance and attire. 53 One article performed an obituary analysis to explore neurosurgical identity. 54…”
Section: Professional Identitymentioning
confidence: 99%
“…This e-survey was reported in accordance with the Checklist for Reporting Results of Internet E-Surveys (CHERRIES), STrengthening the Reporting Of Cohort Studies in Surgery (STROCSS), and Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) [ 11 13 ].…”
Section: Methodsmentioning
confidence: 99%